Marxism, Structuralism and Psychoanalysis : Althusser's Paths of Reception in Argentinian Psychoanalytic Culture (1965-76) - Starcenbaum, Marcelo (Historical Materialism.)
Althusser's reception within Argentinian psychoanalytic culture assumed a variety of different forms. For the purposes of delimiting mediations between Marxism, structuralism and psychoanalysis in Argentina during the 1960s and '70s, this work seeks to reconstruct historical readings of Althusser according to his reception within three distinct interpretative communities. The first group, centring on the figure of Oscar Masotta, concerns Althusser's role in the development of Argentina's incipient Lacanian groups. For the second group, primarily dissident-psychoanalytic and Freudo-Marxist, the reception of Althusser will be considered in tandem with ensuing debates between Freudo-Marxism and Althussero-Lacanism. The third group asks us to consider the role of Althusserianism in discussions around the professionalisation of psychology, where the careers of Carlos Sastre and Roberto Harari showed the strongest connections to Althusser's work.